(untitled) (Journal of science and technology exploration, 2025)
With the rapid development of artificial intelligence technology, the securities industry is undergoing unprecedented and profound changes. This paper systematically analyzes the practical application of AI technology in the front, middle, and back offices of securities institutions and across various business processes, delving into the underlying technological driving logic and the essential transformations within the industry. The study reveals that AI technology has evolved from an auxiliary tool to a core infrastructure of the securities industry. Applications such as Huatai Securities’ "AI Zhang Le" are propelling intelligent investment services from a "functional" to an "intelligent" leap. This paper interprets the essential characteristics of the AI-driven securities industry from three dimensions: technology acceptance, service models, and risk profiles. It highlights current challenges such as model hallucination, data security, and ethical misconduct, and proposes a tiered development pathway and regulatory recommendations. The research indicates that AI technology is reconstructing the value creation model of the securities industry, driving its transformation from experience-driven to data- and intelligence-driven.